2010
DOI: 10.1111/j.1471-4159.2010.06970.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular rearrangement of hsp90‐binding immunophilins accompanies neuronal differentiation and neurite outgrowth

Abstract: Immunophilins (IMMs) are a family of proteins that bind immunosuppressive drugs and possess cis/trans-peptidylprolyl-isomerase activity. They are classified as FKBPs (FK506-binding protein) when they bind FK506, and cyclophilins when they bind cyclosporine A (CsA) . FKBP51 and FKBP52 (gene names FKBP5 and FKBP4, respectively) are highly homologous tetratricopeptide-domain immunophilins whose sequences share 60% identity and 75% similarity. The best characterized interactions of FKBP52 and FKBP51 are with hsp90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 74 publications
(131 reference statements)
5
85
1
4
Order By: Relevance
“…Recent studies demonstrated that in both undifferentiated neuroblastoma cells and embryonic hippocampal neurons, the early subcellular relocalization of FKBP51 and FKBP52 relates to neuronal differentiation and neurite outgrowth (28). During these studies on the subcellular redistribution of immunophilins, we noted that FKBP51 shows a peculiar cytoplasmic pattern compatible with mitochondrial localization.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Recent studies demonstrated that in both undifferentiated neuroblastoma cells and embryonic hippocampal neurons, the early subcellular relocalization of FKBP51 and FKBP52 relates to neuronal differentiation and neurite outgrowth (28). During these studies on the subcellular redistribution of immunophilins, we noted that FKBP51 shows a peculiar cytoplasmic pattern compatible with mitochondrial localization.…”
mentioning
confidence: 79%
“…Whether FKBP51 may use the Hsp90/Hsp70-dependent mechanism for mitochondrial import is still uncertain, although it is possible in view of the requirement of the TPR domain of FKBP51. Recently, it was shown that neuronal FKBP51 also forms complexes with Hsc70 (28). Previous studies have already demonstrated that Hsp70 selectively targets the TPR domains in SGT1 (41) and heat-shock organizing protein (Hop) (42), whereas CyP40 (43) and carboxy terminus of Hsc-70 interacting protein (CHIP) (44) are less discriminatory and can bind either Hsp90 or Hsc70.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect Immunofluorescence Assays-Cells grown on polylysine-coated coverslips were fixed with 3% p-formaldehyde for 30 min and permeabilized with 0.1% Triton X-100 as described (31). Indirect immunofluorescence was performed using 1/100 dilutions of the following primary antibodies: rabbit monoclo-nal IgG anti-FKBP51 (Affinity BioReagents, Golden, CO), MG19 mouse monoclonal IgG anti-FKBP51 (32), UP30 rabbit antiserum against FKBP52 (33), and anti-HA or anti-RelA mouse monoclonal antibodies (Santa Cruz Biotechnology, Dallas, TX) to detect transfected RelA protein or endogenous RelA protein, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…With the same settings, the confocal images were obtained to develop 3D reconstruction images to perform the 3D colocalization analysis as previously described. 57 Assessment of the spinal cord scar and regenerated axons. Quantification of the spinal cord scar, lesion and neurite-regenerated areas were performed using the Fiji program (v.1.45) (NIH; Bethesda, MA, USA) with an area measurement and a calibration/set scale plug-in for the pre-calibration of each image.…”
Section: Methodsmentioning
confidence: 99%